2014
DOI: 10.3390/nu6093895
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Nervosa and Body Fat Distribution: A Systematic Review

Abstract: The aim of this paper was to conduct a systematic review of body fat distribution before and after partial and complete weight restoration in individuals with anorexia nervosa. Literature searches, study selection, method development and quality appraisal were performed independently by two authors, and data was synthesized using a narrative approach. Twenty studies met the inclusion criteria and were consequently analyzed. The review had five main findings. First, during anorexia nervosa adolescent females lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…Since this is the first study to assess body composition in men with anorexia nervosa, we are not able to compare this finding with previous studies in this population. Nevertheless, it should be mentioned that a similar change in body composition patterns has previously been reported in female patients with anorexia nervosa (El Ghoch, Calugi, Lamburghini, & Dalle Grave, ).…”
Section: Discussionsupporting
confidence: 77%
“…Since this is the first study to assess body composition in men with anorexia nervosa, we are not able to compare this finding with previous studies in this population. Nevertheless, it should be mentioned that a similar change in body composition patterns has previously been reported in female patients with anorexia nervosa (El Ghoch, Calugi, Lamburghini, & Dalle Grave, ).…”
Section: Discussionsupporting
confidence: 77%
“…Stool samples were acquired 10.61 ± SD 13.01 days after hospital admission. All AN inpatients were encouraged to adhere to a mixed diet because an appropriate caloric intake helps to avoid refeeding complications and an excessive gain of weight is detrimental and a major risk factor for relapse (El Ghoch, Calugi, Lamburghini, & Dalle Grave, ).…”
Section: Resultsmentioning
confidence: 99%
“…Anorexia nervosa (AN) has one of the highest mortality rates of all psychiatric disorders (Chesney, Goodwin, & Fazel, ). Clinical observations show altered body composition (El Ghoch, Calugi, Lamburghini, & Dalle Grave, ; Solmi et al, ) accompanied by elevated cholesterol (Hussain et al, ) and greater insulin sensitivity (Ilyas et al, ). However, conclusions are limited by small sample sizes and consequent mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed that adolescents and adults differently lose fat tissue when affected by AN, with adolescents losing more central fat tissue and adults more peripheral fat tissue. During weight recovery, individuals with AN show emergent central adiposity which typically attenuates over time (El Ghoch, Calugi, et al, ). These clinical and genetic findings encourage the meta‐analytic reassessment of the role of body composition traits, such as fat mass and fat‐free mass, their regional distribution, and their changes associated with weight restoration and long‐term weight recovery in AN.…”
Section: Introductionmentioning
confidence: 99%